A comparison of German and Indian innovation pathways in the auto component industry - Katharina Kalogerakis; Luise Fischer; Rajnish Tiwari (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2017)
This paper is a part of a series of analyses conducted within a BMBF-funded research project to investigate potentials of frugal innovations for Germany. One of the objectives of this project has been to identify innovation pathways that foster frugal innovations. Since auto component suppliers based in India are known to contribute significantly to the development of 'affordable and good quality' vehicles, it was considered useful to conduct comparative studies of the prevalent innovation pathways in Germany with those in India. This paper is based on our investigations of innovation pathways in Indian and German auto component industries and aims to provide a coherent comparative analysis. After discussing similarities and differences in Indian and German innovation pathways, a reference model for frugal innovation pathways is outlined. The results provide insights on how certain elements of frugal innovation pathways could be implemented in Germany in order to create solutions that are affordable, fulfil the requisite quality standards and avoid unnecessary usage (wastage) of resources. Altogether, exploratory connections are identified which provide impetus for further research and can be thought-provoking for relevant business, social and political stakeholders.
Keywords: 330; Frugal Innovation; Innovation Pathways; Path Dependency; Automotive; Auto-Component Industry